Assessing Loss to Follow-up After Newborn Hearing Screening in the Neonatal Intensive Care Unit: Sociodemographic Factors That Affect Completion of Initial Audiological Evaluation. Issue 2 (14th March 2022) - Cheung, Anthony; Chen, Tammy; Rivero, Rachel; Hartman-Joshi, Kristin; Cohen, Michael B.; Levi, Jessica R.
Abstract : Objectives: Neonatal intensive care unit (NICU) patients are at high risk for congenital hearing loss. Previous studies have found sociodemographic factors associated with loss to follow-up for newborn hearing screening, but none have specifically studied the NICU population. Our objective is to determine if demographics and socioeconomic status is associated with loss to follow-up in a newborn population with extended NICU stay. Design: A retrospective cohort study was conducted on 443 NICU infants with extended NICU stay utilizing data extracted from infant and maternal medical records at an urban safety-net hospital. Results: Younger maternal age (adjusted odds ratio [OR] 0.95, confidence interval [CI] 0.91 to 0.99), higher gravidity (adjusted OR 1.39, CI 1.12 to 1.72), and former smoking status (adjusted OR 2.57, CI 1.07–6.18) were identified as independent predictors of loss to follow-up for NHS after conducting a multivariable logistic regression. Demographic and socioeconomic variables, such as sex, parity, birth weight, mode of birth, highest level of maternal education, maternal race/ethnicity, zip code metrics, and maternal language were not found to be associated with loss to follow-up. Conclusions: Maternal age, gravidity, and smoking status are risk factors for loss to follow-up for NHS in newborns with extended NICU stay, a group at high risk for hearing loss. Our findings demonstrate that socioeconomic and demographic factors for loss to follow-up in the extended-stay NICU population are distinct from the well-baby population. Further investigation of these patients will allow prioritization of limited resources to subgroups within the extended-stay NICU population at risk for loss to follow-up for newborn hearing screening.